Development and adaptation of the methodology for comprehensive assessment of the state of the environment for the territories of administrative regions - Еresko, Мarina; Rodzkin, Aleh (Journal of the Belarusian State University. Ecology, 2023)
Assessment of the state of the environment of certain territories fulfilled for designing large construction projects, assessing the ecological potential of territories and their resistance to external influences, and in other cases. In foreign countries, for a comprehensive assessment of environmental impact, a diverse range of indicators is used, which, as a rule, is linked to specific components that make up the landscape but without the administrative component. The goal of our research was to develop an original methodology for a comprehensive assessment of territories, where an administrative district with a unified management structure and statistical reporting database was proposed as the optimal territorial unit. A total of 10 indicators have been proposed to assess both negative and positive impacts. To adapt the methodology for conducting a comprehensive assessment of the territory, three districts of the Minsk region of Republic of Belarus (Borisovsky, Dzerzhinsky and Myadelsky) were selected, which are characterized by similar climatic conditions, but have serious differences in size, population, specialization and areas of economic activity. The results of the analysis show that the specialization of the district makes a significant contribution to the final assessment. Thus, if the area that develops environmental, recreational and tourist activities (Myadelsky) predictably has a higher final score, but more significant total impact on the environment and, accordingly, a low final assessment is typical for an area with developed agricultural activities.
Keywords: territory; comprehensive assessment; environment; ecological potential; environmental impact